Role of Semiquantitative Assessment of Regional Binding Potential in 123I-FP-CIT SPECT for the Differentiation of Frontotemporal Dementia, Dementia With Lewy Bodies, and Alzheimer's Dementia. (January 2015) - Spehl, Timo S.; Frings, Lars; Hellwig, Sabine; Weiller, Cornelius; Hüll, Michael; Meyer, Philipp T.; Amtage, Florian
<x xml:space="preserve">Abstract</x> Introduction 123I-FP-CIT SPECT is increasingly used to differentiate between Alzheimer's dementia (AD) and dementia with Lewy bodies (DLB). The role of 123I-FP-CIT SPECT in frontotemporal dementia (FTD) is rather unclear, albeit nigrostriatal involvement may occur. The aim of this study was to evaluate its role in the differentiation of FTD, DLB, and AD. Methods We analyzed 34 patients with clinical diagnosis of FTD (n = 13), DLB (n = 12), and AD (n = 9) undergoing combined 18F-FDG PET and 123I-FP-CIT SPECT. We performed a semiquantitative region of interest–based analysis to determine the binding potential values in caudate nucleus, putamen, and whole striatum including the caudate/putamen binding potential ratio and asymmetry indices. The receiver operating characteristic analyses and multinomial logistic regression were conducted to assess discrimination accuracy. Results The putaminal binding potential separated DLB from AD with high accuracy (area under the receiver operating characteristic curve [AUC], 0.94). It also discriminated FTD from DLB with high accuracy (AUC, 0.92), whereas differentiation between FTD and AD was less accurate (AUC, 0.74). The binding potential ratio also provided high accuracy for differentiation of FTD and DLB (AUC, 0.91). Combination of these 2 parameters yielded slightly higher results for differentiation of FTD and DLB (AUC, 0.97). In a group including all patients, accuracy remained very high for DLB (AUC, 0.95), whereas values for FTD (AUC, 0.81) and AD (AUC, 0.80) were lower. Conclusions Semiquantitative assessment of striatal dopamine transporter availability can differentiate between FTD and DLB as well as DLB and AD with high accuracy, whereas discrimination between AD and FTD is limited.